2021
DOI: 10.1101/2021.11.29.470107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping SOX9 transcriptional dynamics during multi-lineage differentiation of human mesenchymal stem cells

Abstract: The master transcription factor SOX9 is a key player during chondrocyte differentiation, cartilage development, homeostasis and disease. Modulation of SOX9 and its target gene expression is essential during chondrogenic, osteogenic and adipogenic differentiation of human mesenchymal stem cells (hMSCs). However, lack of sufficient knowledge about the signaling interplay during differentiation remains one of the main reasons preventing successful application of hMSCs in regenerative medicine. We previously showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 45 publications
(64 reference statements)
5
4
0
Order By: Relevance
“…This indicates that different subpopulation of cells do not respond to differentiation stimuli of particular lineage and only selected subpopulation of cells can differentiate into a particular lineage. These data are also in line with our previous findings with SOX9 dynamics in hMSCs (16).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This indicates that different subpopulation of cells do not respond to differentiation stimuli of particular lineage and only selected subpopulation of cells can differentiate into a particular lineage. These data are also in line with our previous findings with SOX9 dynamics in hMSCs (16).…”
Section: Discussionsupporting
confidence: 93%
“…We have shown that number of cells present per subpopulation might determine differentiation potential of a donor towards a particular lineage. Our RUNX2 dynamics study confirms our findings in our previous similar study on SOX9 dynamics in hMSCs (16).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations